Macula Structure and Microvascular Changes in Recent Small Subcortical Infarct Patients - Cao, Yungang; Yan, Jueyue; Zhan, Zhenxiang; Liang, Yuanbo; Han, Zhao (Frontiers in Neurology, 2021)
Purpose: To assess the macula structure and capillary plexus in the macula and around the optic nerve in patients with recent small subcortical infarct (RSSI) Methods: This observational cross-sectional study included 40 RSSI patients and 46 healthy controls who were sex- and age-matched. Spectral domain optical coherence tomography (SD-OCT) was used to image and measure the peripapillary retinal nerve fiber layer (pRNFL) thickness, microvascular density within the radial peripapillary capillaries (RPCs), superficial retinal capillary plexus (SRCP) and deep retinal capillary plexus (DRCP) densities among the two groups. Data for the macula parameters were generated automatically by the OCT tool. Results: Microvascular density in the RPC (P < 0.001), SRCP (P = 0.001) and DRCP (P = 0.003) were significantly reduced in RSSI patients when compared to healthy controls. The pRNFL thickness was significantly reduced (P < 0.001) in RSSI patients when compared to healthy controls. In the RSSI group, the SRCP density significantly correlated with the DRCP density (Rho = 0.381, P = 0.042). The pRNFL thickness showed a significant correlation with the RPC density (Rho = 0.482, P = 0.003) in the RSSI group. Conclusions: RSSI patients showed interrupted capillary plexus and significantly reduced capillary density in the macula and around the optic nerve head. Our reports provide insight into the macula capillary microcirculation changes in RSSI.